Design and Fabrication of Horizontal Screw Type Mixer for Livestock Feed Meal - Cajindos, Jayson Reynante (JPAIR Multidisciplinary Research, 2014)
Small-scale livestock raisers are in dire need of a highly nutritious poultry feed to increase production output. And efficient mixing is the next key to good feed production. The mixing time for a batch of ingredients varies according to the design of the mixer, thus designing a fabricated horizontal screw type mixer was necessitate. The horizontal screw type mixer for livestock feed meal was fabricated using metal working concepts. The main components are the housing, bucket, rotor assembly and gear box. Experimental design was made to obtain the machine performance like pulley ratio, number of paddles/ blades, and the driving gear ratio. The machine used four (4) inches diameter pulley at the gear box and seven (7) inches diameter pulley at the gear box and seven (inches) diameter pulley at the motor connecting with a V-belt, eight paddles were installed at the rotor shafting for good mixing capability. The driving gear used 18 teeth at the upper sprocket and 36 teeth at the lower sprocket to obtain past and efficient mixing of raw materials in the production of feeds. It is powered by one half horse power electric motor. The machine could produce in an average of 15 kilograms in two (3.66) minutes.
Keywords: Fabricated Horizontal Screw Mixer; Livestock Feeds; Vigan City; Ilocos Sur; Philippines